2015
DOI: 10.3390/en81011955
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Effects ofWinglets on the Wake and Performance of a ModelWind Turbine

Abstract: Wind tunnel experiments were performed to investigate the effects of downstream-facing winglets on the wake dynamics, power and thrust of a model wind turbine. Two similar turbines with and without winglets were operated under the same conditions. Results show an increase in the power and thrust coefficients of 8.2% and 15.0% for the wingletted case. A simple theoretical treatment of a two-turbine system suggests a possible positive tradeoff between increasing power and thrust coefficients at a wind farm scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 24 publications
3
33
0
Order By: Relevance
“…The time‐averaged mean streamwise flow is generally seen to compare well for both blade tip configurations, while the only significant difference is a wider initial wake extension after the wingletted rotor. This finding agrees well with earlier observations by Shimizu et al, Johansen and Sørensen, Tobin et al, and Ostovan et al Ostovan et al also measured a wider wake extension and thicker mixing layer in the very near wake behind a three‐bladed wingletted rotor. A closer look into the fluctuating quantities in the wake revealed significant differences between the two investigated configurations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The time‐averaged mean streamwise flow is generally seen to compare well for both blade tip configurations, while the only significant difference is a wider initial wake extension after the wingletted rotor. This finding agrees well with earlier observations by Shimizu et al, Johansen and Sørensen, Tobin et al, and Ostovan et al Ostovan et al also measured a wider wake extension and thicker mixing layer in the very near wake behind a three‐bladed wingletted rotor. A closer look into the fluctuating quantities in the wake revealed significant differences between the two investigated configurations.…”
Section: Discussionsupporting
confidence: 92%
“…An analysis of the streamwise velocity showed a wider wake extension for the wingletted configuration. Another PIV study of the wake up to xfalse/D = 5 behind a significantly smaller rotor of D = 0.12 m with and without winglets was conducted by Tobin et al Their PIV study indicated an increased velocity deficit in the wake of the wingletted rotor. Although another downstream turbine, which was operated in the wake, was found to produce less power, the combined power of the two‐turbine array could be increased by the use of winglets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the light of the above-mentioned benefits of wind tunnel experiments, they have been widely used in the wind-energy community to study wind turbines and their wakes (e.g., [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]). However, …”
Section: Introductionmentioning
confidence: 99%
“…The geometry of the representative rotor is based on a reference model turbine designed at Sandia National Laboratory [34,35]. A Precision Microdrive 112-001 Micro Core 12 mm Direct Current (DC) motor acted as the loading system, which resulted in a rated power P 0 ∼ 1 W [8,36]; additional information on the model turbine can be found in Tobin et al [37]. The two wind farm layouts consisted of aligned turbines with streamwise separation of S x = ∆x T /d T = 5 and 10, which shared the same spanwise separation of S y = ∆y/d T = 2.5.…”
Section: Methodsmentioning
confidence: 99%